Arctic Alpine Ecosystems and People in a Changing Environment - Ørbaek, Jon Børre; Kallenborn, Roland; Tombre, Ingunn; Hegseth, Else N.; Falk-Petersen, Stig; Hoel, Alf H. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
This book addresses the significant environmental changes experienced by high latitude and high altitude ecosystems at the beginning of the 21st c- tury. Increased temperatures and precipitation, reduction in sea ice and glacier ice, the increased levels of UV-radiation and the long-range tra- ported contaminants in arctic and alpine regions are stress factors that challenge terrestrial and aquatic ecosystems. The large natural variation in the physical parameters of these extreme environments is a key factor in structuring the biodiversity and biotic productivity, and the effect of the new stress factors can be critical for the population structures and the - teraction between species. These changes may also have socio-economic effects if the changes affect the bio-production, which form the basis for the marine and terrestrial food chains. The book is uniquely multidisciplinary and provides examples of va- ous aspects of contemporary environmental change in arctic and alpine - gions. The 21 chapters of the book are organised under the fields of •Climate change and ecosystem response, •Long range transport of poll- ants and ecological impacts, and •UV radiation and biological effects, each also including aspects of the •Socio-economic effects of environmental change. The introductory chapter presents and explains the internal c- nection and integration of all chapters. The added value of these reviews and review-like manuscripts from different disciplines hopefully yields new information about the integrated aspects of environmental change.